DEVELOPMENT OF ENGLISH DAILY CONVERSATION POCKETBOOK TO TEACH ENGLISH SPEAKING SKIILS FOR BILINGUAL PROGRAM AT MTS PLUS AL-AZHAR WLINGI - Visa Izza Maulidy; Istina Atul Makrifah; Siti Rofi'ah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The effectiveness of the learning process decreases when teachers do not use appropriate media for teaching. Students become passive as they struggle to focus on studying English speaking skills due to a lack of knowledge on what to speak and difficulties in speaking. Therefore, a learning media is necessary to teach and improve students' speaking skills. One such media is the English Daily Conversation Pocketbook. The study aims to determine the enhancement of students' understanding and practice of English in their daily activities, especially within the Bilingual Program at MTs Plus Al-Azhar Wlingi. This research follows a Research and Development method with seven cycles, focusing on 8th-grade students (10 students). Data collection techniques included interviews and tests, with qualitative and quantitative data analysis. The results from the validators' questionnaire showed a 90% approval rate, indicating the media's suitability. Additionally, student test results after using the media showed an improvement from an average score of 66 to 86.4, with an N-Gain score of 0.544, indicating moderate and effective criteria for use in the Bilingual Program